2015
DOI: 10.1111/acem.12729
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility ofEscherichia coliin Uncomplicated Cystitis in the Emergency Department: Is the Hospital Antibiogram an Effective Treatment Guide?

Abstract: Objectives: The objective was to compare the rates of antimicrobial susceptibility in strains of Escherichia coli isolated from uncomplicated cystitis cases presenting to the emergency department (ED) of a tertiary care center to those reported on that institution's hospital-wide antibiogram. The hypothesis was that cases of uncomplicated cystitis presenting to the ED will exhibit higher antimicrobial susceptibility than is reported by the hospital-wide antibiogram.Methods: A retrospective chart review of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
5
1
3
Order By: Relevance
“…Interestingly, we observed lower E. coli susceptibility overall in the ED cohort compared to the institution-wide antibiogram. This finding is in contrast to previous studies in the ED setting in which higher susceptibility rates were noted compared to the institution-wide antibiogram (7)(8)(9). The different patient populations included may have contributed to the differences observed between studies.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, we observed lower E. coli susceptibility overall in the ED cohort compared to the institution-wide antibiogram. This finding is in contrast to previous studies in the ED setting in which higher susceptibility rates were noted compared to the institution-wide antibiogram (7)(8)(9). The different patient populations included may have contributed to the differences observed between studies.…”
Section: Discussioncontrasting
confidence: 91%
“…The different patient populations included may have contributed to the differences observed between studies. Other investigators have focused primarily on premenopausal females presenting to the ED with uncomplicated UTI (7,8) or patients with UTI and stable for discharge (9). Our population was comprised of a large proportion of older individuals with a high burden of comorbid conditions, previous antibiotic exposure, and multiple factors predisposing to a more complicated disease process.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, both urine and pus isolates showed only 25% to 35% sensitivity to fluoroquinolones. Tailoring antibiograms and treatment recommendations to better match specific patient populations could improve patient care, simplify treatment regimens, improve antimicrobial stewardship, and reduce health care costs (Christian Smith et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Using AST data from single patient isolates recovered from different sources would enable search parameters to include the selection of both specimen type [55][56][57][58][59][60] and specific organisms [59][60][61] , thereby providing more realistic algorithms to guide empiric treatment. Antimicrobial prescription and institutional antibiograms differ between various institutions, sometimes even within an individual health-care institution 60,62,63 , and between inpatient and outpatient populations 60,[63][64][65] . They may change on the basis of length of hospital stay 66 and may depend on the age of the patient 65,67 .…”
Section: The Institutional Antibiogrammentioning
confidence: 99%